2022
DOI: 10.1039/d2dt02518c
|View full text |Cite
|
Sign up to set email alerts
|

An anionic Zn-MOF composed of 1D columnar SBUs for highly C2H2/CH4 selective adsorption, dye adsorption and fluorescence sensing

Abstract: An anionic three-dimensional framework {(Me2NH2)2[Zn8(L)6(ad)4(μ4-O)]·10DMF·11H2O}(Zn-MOF, L2-=4,4'-(3-aminopyridine-2,5-diyl)dibenzoic acid, ad-=adeninate) with a column-layered structure was synthesized. Structural studies show that the Zn-MOF has octahedral cages [Zn8(ad)4(μ4-O)], adjacent cages are connected by O...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The C 2 H 2 and CO 2 uptake amounts of In-MOF 2 exceeded those of some other In-MOFs at 273 K and 298 K, such as [Me 2 NH 2 ][In(L)]·2.5NMF·4H 2 O (85/59 cm 3 g −1 , 65/30 cm 3 g −1 ) 12 SNNU-150-In (50/35 cm 3 g −1 and 40.2/23 cm 3 g −1 ), 19 BUT-70A (93.8/69.5 cm 3 g −1 and 37.9/19.3 cm 3 g −1 ) 20 and Zn-MOF (98.61/59.79 cm 3 g −1 and 54.27/33.10 cm 3 g −1 ). 21 It is worth noting that the pore size distributions showed that the pore size of In-MOF 2 is mainly distributed at 5.89 Å, which is less than 6.79 Å of In-MOF 1 . In-MOF 2 displayed larger C 2 H 2 and CO 2 uptakes than In-MOF 1 , despite the narrower pore size.…”
Section: Resultsmentioning
confidence: 89%
“…The C 2 H 2 and CO 2 uptake amounts of In-MOF 2 exceeded those of some other In-MOFs at 273 K and 298 K, such as [Me 2 NH 2 ][In(L)]·2.5NMF·4H 2 O (85/59 cm 3 g −1 , 65/30 cm 3 g −1 ) 12 SNNU-150-In (50/35 cm 3 g −1 and 40.2/23 cm 3 g −1 ), 19 BUT-70A (93.8/69.5 cm 3 g −1 and 37.9/19.3 cm 3 g −1 ) 20 and Zn-MOF (98.61/59.79 cm 3 g −1 and 54.27/33.10 cm 3 g −1 ). 21 It is worth noting that the pore size distributions showed that the pore size of In-MOF 2 is mainly distributed at 5.89 Å, which is less than 6.79 Å of In-MOF 1 . In-MOF 2 displayed larger C 2 H 2 and CO 2 uptakes than In-MOF 1 , despite the narrower pore size.…”
Section: Resultsmentioning
confidence: 89%
“…Moreover, the treatment of wastewater containing various pollutants, which threaten the aquatic environment and life quality, has been of great interest with increasing industrialization. Among the pollutants, dyes are one of the most prevalent pollutants in wastewater due to their wide employment in diverse industries such as textile, food, leather, cosmetics, printing, paper, etc. Hence, the removal of dye pollution before being discharged into the environment has gained increased attention due to its toxicity, stability, and reduction in the oxygen content in aquatic media. So far, for this purpose, several methods, e.g., adsorption, degradation, oxidative decomposition, and coagulation, have been applied. Among the methods, adsorption is considered one of the simple, convenient, and effective wastewater treatment methods to remove dyestuff from aquatic media . Several conventional adsorbents have been used for the remediation of dyestuff. However, due to their poor selectivity and weak adsorption capacity, recently, MOFs have attracted attention as adsorbents for dye removal due to their tunable properties and high adsorption capacity. , MOFs with anionic or cationic skeletons (with charged surfaces) can separate the dye from the dye mixture (selective adsorption) via electrostatic interactions. , In addition, adsorption capacity and selective adsorption can be enhanced with hydrogen bonding or π···π interactions between MOFs and dye molecules …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16] As we all know, the structure of MOFs mainly depends on the selection and design of ligands. Pyridine in ligands can change the flexibility of the skeleton, 17,18 and the coordinated N atom in the structure can affect the gas adsorption of MOFs. 19 Therefore, the combination of pyridines and nitrogen-containing organic small molecule ligands makes the synthesized MOFs more diversified in structure and more stable in performance.…”
Section: Introductionmentioning
confidence: 99%